Analisis Keterampilan Menulis Teks Narasi pada Siswa Kelas IV di SDN Pati Kidul 03 - Melinda Khoriyah Ningrum; Dimas Agus Dwi Saputro; Rani Setiawaty (Institut Nalanda, 2024)
This research aims to analyze the learning of narrative text writing skills, and the factors of narrative text writing skills. The type of research is descriptive qualitative with a case study approach. This research was conducted in class IV of SDN Pati Kidul 03 Pati Regency. Data collection techniques in this research were carried out in several ways, namely: observation, interviews, and documentation. The subjects in this research were the class IV homeroom teacher and 30 class IV students. The instruments in this research are the main and supporting instruments, the main instrument is the researcher himself, and the supporting instruments are observation sheets, interview guides, cell phones, pens and books. The results of this research can be concluded (1) The level of ability of class IV students is good, this can be seen from the assessment of the students, (2) Factors in the Ability to Write Narrative Texts in the implementation of learning. Students still lack understanding and difficulty in writing narrative essays. caused by internal and external factors.